Correlation Between Reading Anxiety and Reading Comprehension of Students at SMA Negeri 3 Palu - Uswathun Nadilla; Mukrim; Maf’ulah; Rofiqoh (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This research aims to investigate the correlation between reading anxiety and reading comprehension of the eleventh grade students of SMA Negeri 3 Palu. This research employed a correlation research design. The sample was 31 students which was taken by using a purposive sampling technique. The data were collected through a reading anxiety questionnaire and reading comprehension test. All the data gained in this research were analyzed using Pearson Product Moment Correlation. The results indicated that there was no significant correlation between anxiety and reading comprehension of the eleventh grade students at SMA Negeri 3 Palu. The correlation coefficient was 0.116, while the significance value ( p = 0.533) was much greater than 0.05, confirming the lack of a significance. This indicates that students’ ability to comprehend texts is not necessarily affected by their level of reading anxiety, suggesting that other factors may contribute to their reading comprehension, such as motivation, reading strategies, limited vocabulary, and the learning environment.